PENGARUH PENAMBAHAN EKSTRAK KULIT BUAH MANGGIS (Garcinia mangostana L.) TERHADAP KARAKTERISTIK JELLY DRINK - Ulfa, Nada; Yusasrini, Ni Luh Ari; Ina, Putu Timur (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This research aimed was to identify the effect of mangosteen skin extract addition towards the characteristics of jelly drink and also to identify the precise of jelly drink with the best characteristics. This reseach used Completely Randomized Design (CRD) with the treatment of adding mangosteen skin which consists of six levels; 10g, 20g, 30g, 40g, 50g, 60g. Each treatment was repeated 3 times, so it resulted in 18 experimental units. The data were then analyzed with the Analysis of Variance method and if the treatment had an effect on the variable, the Duncan test w as performed. The results show ed that mangosteen skin extract s i ginificant ly affect ed the level of vitamin C, antioxidant activity, hedonic (color and overall acceptance), scor (color and taste), Non significant effect to taste and the overall acceptance of mangosteen skin extract jelly drink. The addition of 60g mangosteen skin result ed in the best characteristic according the following criteria: 54;85 mg AAE/g vitamin C, 96;81% antioxidant activity, red color and liked, texture liked, taste netral and rather tight, and overall acceptance liked.   Keyword: mangosteen skin, jelly drink, characteristics, antioxidant